Hybrid chemistry. Part 4: Discovery of etravirine–VRX-480773 hybrids as potent HIV-1 non-nucleoside reverse transcriptase inhibitors. Issue 15 (1st August 2015) - Wan, Zheng-Yong; Tao, Yuan; Wang, Ya-Feng; Mao, Tian-Qi; Yin, Hong; Chen, Fen-Er; Piao, Hu-Ri; De Clercq, Erik; Daelemans, Dirk; Pannecouque, Christophe
Graphical abstract: Abstract: A novel series of etravirine–VRX-480773 hybrids were designed using structure-guided molecular hybridization strategy and fusing the pharmacophore templates of etravirine and VRX-480773. The anti-HIV-1 activity and cytotoxicity was evaluated in MT-4 cell cultures. The most active hybrid compound in this series, N -(2-chlorophenyl)-2-((4-(4-cyano-2, 6-dimethylphenoxy)pyrimidin-2-yl)thio)acetamide 3d (EC50  = 0.24, SI >1225), was more potent than delavirdine (EC50  = 0.66 μM, SI >67) in the anti-HIV-1 in vitro cellular assay. Studies of structure-activity relationships established a correlation between anti-HIV activity and the substitution pattern of the acetanilide group.